Un estudio acerca de "dos astros menores" en la obra de Benjamín Jarnés: Cardenio y Altisidora - Muñoz Covarrubias, Pablo (El Colegio de México, 2017)
Reception: January 13, 2016.Accepted: June 6, 2016.Without any doubt, Benjamín Jarnés’ novels and short stories represent one of the most interesting manifestations of Avant Gard prose in Spain. The purpose of this article is to explore a wide range of texts in order to understand the importance of Cervantes in the literary creations of Jarnés. In particular, the article focuses on two Cervantine characters who appear in several of the modern author’s books: Cardenio and Altisidora. In each case, Jarnés is interested in recreating and transforming both characters in order to create new and original interpretations. For Jarnés, both Cardenio and Altisidora possess mythical dimensions.